Anti-recoverin antibodies in a cerebellar syndrome without retinal involvement - Minetti, Matteo; Balella, Giulia; Zinno, Lucia (Acta Biomedica Atenei Parmensis, 2023)
Anti-recoverin antibodies are typically found in cancer-associated retinopathy or autoimmune diseases. We present a case of anti-recoverin positive cerebellar syndrome without any signs of malignancy or retinopathy. The patient was treated with steroids and intravenous immunoglobulins, resulting in improvements in both cognitive and motor symptoms.